Preparation and biological evaluation of novel acylhydrazide derivatives of 2,3-dichloronaphthoquinone - Elaridi, Jomana (2017)
Naphthoquinones have been reported to possess a variety of pharmacological properties including antibacterial, antifungal, antiviral, anti-inflammatory, anti-artherosclerotic and anticancer effects. We have successfully synthesized a series of novel naphthoquinone acylhydrazides. The straightforward synthesis of these molecules involves a coupling reaction between 2,3-dichloro-1,4-naphthoquinone and several alkyl and aromatic hydrazides and the hydrazides of the pyrimidine nucleobases, uracil and thymine. The product hydrazides were isolated in good yields and completely characterized by spectroscopic analysis. Biological evaluation against human colon cancer HCT116 cells and human breast cancer MCF-7 cells indicated that the novel hydrazides possessed significant anticancer activity.